Evaluation of Efficacy and Plasma Concentrations of Ropivacaine in Continuous Axillary Brachial Plexus Block: High Dose for Surgical Anesthesia and Low Dose for Postoperative Analgesia. Issue 1 (1st January 2000) - Salonen, Merja H.A.; Haasio, Juhani; Bachmann, Martina; Xu, Mei; Rosenberg, Per H.
Abstract : Background and Objectives: Ropivacaine is a potent local anesthetic that, experimentally at low concentrations, produces an effective block of pain conducting nerve fibers. Therefore, it was hypothesized that 0.1% and 0.2% ropivacaine would provide clinically adequate postoperative analgesia in continuous axillary plexus block. Methods: Sixty patients (ASA I-II) scheduled for elective hand or forearm surgery received 5 mg/kg of 0.75% ropivacaine for axillary block using nerve stimulator technique. One hour later, in random order, a continuous infusion of either 0.1% ropivacaine (0.125 mg/kg/h), 0.2% ropivacaine (0.25 mg/kg/h) or saline 6 to 11 mL/h was started. Results: The mean total ropivacaine dose for the surgical block was 5.1 to 5.2 mg/kg with the supplementation. All patients were pain free for the first 12 to 15 hours after the block. The need for postoperative analgesics during the infusion was similar in all groups. After the initial block, the maximum plasma concentrations (mean 2.5 μg/mL) were measured at 45 or 60 minutes after injection. The highest individual plasma concentration was 4.2 μg/mL. Despite the high venous peak concentration, no toxic reactions were observed. The mean peak plasma concentration (Cmax ) was 2.2 ± 0.5 μg/mL for saline, 2.6 ± 0.8 μg/mL for 0.1% ropivacaine, and 2.6 ± 0.7 μg/mL for 0.2% ropivacaine. During the continuous infusion of 24 hours, the ropivacaine concentration declined steadily. Conclusions: Ropivacaine is safe and effective for axillary brachial plexus block. The continuous infusion of 0.1% or 0.2% ropivacaine was no more beneficial than an infusion of saline in relieving postoperative pain in patients having elective hand surgery. None of the infusions were sufficient to adequately treat the patients' pain without the addition of adjunct agents.